Substitutional Lithium Doping on Germanene: A First-principles Study - Basel, J.; Pantha, N. (Journal of Nepal Physical Society, 2021)
The density functional theory (DFT) based first-principles calculations have been adopted for the study of structural, electronic and magnetic properties of pure and single Lithium (Li) atom doped germanene monolayer. Due to the higher intrinsic carrier mobilities and large spin orbit gap, germanene has great possibility of being integrated into the silicon based semiconductor industry. Different studies have been done to change the band gap value from its’ pristine zero band gap state. We have doped the single Li atom into the germanene system with the intention of tuning the band gap and other electronic and magnetic properties. Band structure calculations show pristine germanene is semi-metallic in nature whereas the Li doped system is fully metallic with the overlapping of the conduction and valance bands in the Fermi level. Under density of states (DOS) calculations, it is evident that both pristine and doped system are non-magnetic in nature with symmetric DOS plot.